2009
DOI: 10.1038/ejhg.2009.163
|View full text |Cite
|
Sign up to set email alerts
|

Chromosome aberrations involving 10q22: report of three overlapping interstitial deletions and a balanced translocation disrupting C10orf11

Abstract: Interstitial deletions of chromosome band 10q22 are rare. We report on the characterization of three overlapping de novo 10q22 deletions by high-resolution array comparative genomic hybridization in three unrelated patients. Patient 1 had a 7.9 Mb deletion in 10q21.3-q22.2 and suffered from severe feeding problems, facial dysmorphisms and profound mental retardation. Patients 2 and 3 had nearly identical deletions of 3.2 and 3.6 Mb, the proximal breakpoints of which were located at an identical low-copy repeat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 12 publications
0
21
0
Order By: Relevance
“…Larger deletions involving KAT6B and other surrounding genes were recorded in three patients (11) and likely also in an older case of a 10q22.1-q22.3 deletion but without defined breakpoints (12). All these patients had developmental delay, intellectual disability and hypertelorism; and at least some were diagnosed with growth deficiency, retarded psychomotor development, absent or reduced speech, hypotonia, sensorineural hearing loss, delayed myelination, post-natal respiratory problems, feeding problems, large anterior fontanel, downslanting palpebral fissures, strabismus, posteriorly rotated ears, short nose, smooth philtrum, microstomia, retrognathia, dental lamina cysts, long/lean/finger-like thumbs, clinodactyly, genital anomalies and diastasis recti.…”
mentioning
confidence: 99%
“…Larger deletions involving KAT6B and other surrounding genes were recorded in three patients (11) and likely also in an older case of a 10q22.1-q22.3 deletion but without defined breakpoints (12). All these patients had developmental delay, intellectual disability and hypertelorism; and at least some were diagnosed with growth deficiency, retarded psychomotor development, absent or reduced speech, hypotonia, sensorineural hearing loss, delayed myelination, post-natal respiratory problems, feeding problems, large anterior fontanel, downslanting palpebral fissures, strabismus, posteriorly rotated ears, short nose, smooth philtrum, microstomia, retrognathia, dental lamina cysts, long/lean/finger-like thumbs, clinodactyly, genital anomalies and diastasis recti.…”
mentioning
confidence: 99%
“…However, CNVs at 10q22 are rare given that no LCRs are located in this interval. Only eight patients with de novo deletions at 10q22 have been delineated [7,[11][12][13][14][15], whereas the reciprocal duplications have never been described to date. In this study, we reported two unrelated patients with de novo overlapping duplications at 10q22 separately, who presented with similar clinical features including speech impairments, behavior problems, dysmorphic features, genital anomalies, developmental delay and intellectual disability.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have shown that KAT6B-related disorders are mainly caused by either nonsense or frameshift mutations in the KAT6B gene that lead to premature truncation of the protein [20][21][22][23][24]. It is noted that individuals with larger 10q22 deletions involving KAT6B gene do not appear to have classic facial features of SBBYSS, but present with some features overlapping those of SBBYSS [7,[11][12][13][14]. Furthermore, Preiksaitiene et al reported a female patient carrying a de novo deletion at 10q22.1q22.3, who presented with immobile mask-like face, blepharophimosis/ptosis, hypotonia, congenital heart defect, developmental delay and intellectual disability which were major features for SBBYSS.…”
Section: Citationmentioning
confidence: 99%
See 1 more Smart Citation
“…The deletion was identified by conventional G-banding. Later, chromosomal microarray testing (CMT) detected similar microdeletions in several other patients (Bartnik et al 2014;Lei et al, 2016;Reddy et al 2011;Tzschach et al 2010).…”
Section: Introductionmentioning
confidence: 99%